Low temperature growth of ZnO thin films by filtered cathodic vacuum arc technique - Lee, Hiong Weng (2008)
A detailed study of zinc oxide films prepared by filtered cathodic vacuum arc technique was carried out, with an emphasis on the application of ZnO as transparent conductive oxide, as well as the fabrication of a ZnO-based transparent thin film transistor.